Efektivitas Evaluasi Pembelajaran Daring Mata Pelajaran Fiqih Menggunakan Google Formulir pada Kondisi Pandemi COVID-19 - Mukhlisin, Mukhlisin; Mubtadik, Mohamad Ayyub; Isroatin, Siti (IERA, Islamic Education and Research Academy, 2020)
This research aims to improve the effectiveness of online learning evaluation using Google Forms in the subject of Fiqh in MTS Darul Hikam Kencong Jambi Baron during the COVID-19 pandemic in the academic year 2020/2021 through classroom action research. The research was conducted in two cycles, each consisting of four stages: planning, implementation, observation, and reflection. The research subjects were 30 students of class VIII in MTS Darul Hikam Kencong Jambi Baron. Data were collected using tests and questionnaires, and analyzed using qualitative and quantitative descriptive analysis techniques. The results showed that the implementation of Google Forms in online learning evaluation in the subject of Fiqh could improve the effectiveness of learning evaluation. In Cycle I, there was a 26.67% increase in the effectiveness of evaluation with a percentage of students' learning mastery of 73.33%. Meanwhile, in Cycle II, there was a 30% increase in the effectiveness of evaluation with a percentage of students' learning mastery of 90%. These results indicate that the use of Google Forms is effective in improving the effectiveness of online learning evaluation in the subject of Fiqh in MTS Darul Hikam Kencong Jambi Baron during the COVID-19 pandemic in the academic year 2020/2021. Therefore, it is recommended that teachers use Google Forms in online learning evaluation to improve the effectiveness of learning evaluation.